The roles of different photoselective nets in the targeted regulation of metabolite accumulation, wine aroma and sensory profiles in warm viticulture regions. (1st December 2022) - Li, Wanping; Liu, Min; Chen, Keqin; Zhang, Jinsheng; Xue, Tingting; Cheng, Zhenglong; Zhang, Bo; Zhang, Kekun; Fang, Yulin
Graphical abstract: Highlights: Shading reduced sugar accumulation in berries and alcohol levels in resulting wines. Red and black nets increased the tannins, flavanols and aromatic volatiles of wines. Wines made from net-covered grapes showed an improvement in sensory characteristics. The red net was associated with the highest comprehensive score among the treatments. Abstract: To improve the quality of grapes and wine in warm viticulture regions, the effects of pearl, red and black photoselective nets on the quality of grapes and wine were systematically investigated. Compared with the CK (open field), three nets improved the microclimate conditions and reduced grape sugar and wine alcohol levels. However, the nets differentially affected other quality profiles of the grapes and wine. The pearl net reduced the total flavanol contents in grapes and total aromatic volatiles in wine. The red net increased the total flavanol, tannin and total aromatic volatile contents in wine by approximately 40%, 95% and 10%, respectively, and the percentages for the black net were 30%, 45% and 3%, respectively. The red and pearl nets were more inclined to improve the taste and aroma sensory qualities of wine than the black net did. The red net had the highest comprehensive scores via principal component analysis.